Talking with consumers about energy reductions: recommendations from a motivational interviewing perspective - Klonek, Florian E.; Kauffeld, Simone (Frontiers in Psychology, 2015)
Reduction of energy costs has become a concern for many organizations. First, we review energy-saving studies in organizations in which consumers showed resistance to change their behavior. Second, we relate resistance to change to the psycholinguistic construct ‘sustain talk’ that describes verbal arguments against behavior change (e.g., “Work processes have priority here”). Third, we argue how Motivational Interviewing (MI) – an interaction-approach to facilitate behavior change – might be helpful in dealing with this behavior. We transfer MI to interactions about energy-savings in organizations and demonstrate how qualification in MI for energy managers may affect these interactions. Therefore, we present three short case scenarios (i.e., video vignettes) that demonstrate socio-interactional mechanisms underlying energy-relevant decisions and behaviors. Consumer’ verbal responses are graphed as one single time-variant index of readiness versus resistance (R-index) in order to illustrate interactional dynamics. In sum, we combine theoretical and empirical perspectives from multiple disciplines and discuss an innovative socio-interaction approach that may facilitate energy-efficient behavior in organizations.